Persepsi Masyarakat tentang Pentingnya Pendidikan Agama Islam bagi Anak Usia Dini di Gang Bendi Bukittinggi - Andini, Zenika; Rivauzi, Ahmad (YASIN, 2025)
The implementation of informal religious education such as the Taman Pendidikan al-Qur’an (TPA) for early childhood in Gang Bendi, Bukittinggi City, reflects a concerning condition, where religious educational activities have ceased due to the absence of child participation. This is especially troubling given the vital role of TPA in shaping children's character and morals from an early age. This study aims to describe the community’s socio-religious conditions, explore public perceptions of the urgency of Islamic Religious Education for young children, and analyze the opportunities and challenges in its implementation. A descriptive qualitative method was employed, using purposive sampling to select ten informants relevant to the study’s focus. The findings indicate that the low participation of early childhood children in TPA is influenced by weak socio-religious conditions and a limited perception of the importance of religious education. Key challenges identified include inadequate facilities and infrastructure. The study concludes that raising community awareness and encouraging active involvement in voicing educational needs to the government are critical factors in revitalizing effective Islamic education in Gang Bendi. These findings underscore the importance of strengthening collaboration between the community and government in supporting early childhood religious education.